PENERAPAN ARSITEKTUR NEO-VERNACULAR PADA PERANCANGAN SANGGRALOKA SAO NGADA DI NGADA, NUSA TENGGARA TIMUR - Dyan Prastyo; Tri Endangsih; Inggit Musdinar Sayekti Sihing Yang Mawantu (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2023)
Indonesia is a country rich in natural resources, since the beginning of the creation of nature with a variety of wealth and beauty is a support for the welfare of human life, which humans live in and can live on the results of nature. It can be said that humans are very dependent on nature. Nature and all of it have been created in such a way by God Almighty with extraordinary beauty to be enjoyed by humans, both mountain scenery, waters, and flora and fauna in it and also community culture which is the result of human civilization, one of which is architecture. Ngada Regency is a district in the central part of the island of Flores, East Nusa Tenggara province, Indonesia. The capital of the district is Bajawa. The area is 1,645.88 Km2 with a population of 132,716. Ngada Regency has three major tribes, namely the Nagekeo Tribe, the Bajawa Tribe and the Riung Tribe. Ngada Regency is one of the regions in East Nusa Tenggara Indonesia has become a tourist destination for both domestic and foreign tourists, tourist destinations in Ngada Regency include natural tourism, cultural tourism, religious tourism, and agro-tourism. This has a positive impact because the number of tourists visiting is increasing.